The distribution of meranti timber species in UiTM Jengka forest reserve / Siti Aminah M. Zainal, Siti Nurashikin Abraham and Wan Shamsyila Wan Mohd @ Wan Mohd Nawi - M. Zainal, Siti Aminah; Abraham, Siti Nurashikin; Wan Mohd @ Wan Mohd Nawi, Wan Shamsyila (2008)
A research was done to study the distribution of Meranti Species in UiTM Jengka Forest Reserve (UiTMJFR). This study area is about 250 acre and contains 20 lines. The method of study used is 5m from left and 5m from right in each line. A total of Meranti Species has been found is categorized based on range diameter breast height (DBH) more than 10cm and above. In this study, the total amounts' of Meranti Species were found are 486 trees with 9 species. There were Meranti Tembaga (Shorea leprosula), Meranti Sarang Punai (Shorea parvifolia), Meranti Belang (Shorea resinosa), Meranti Rambai Daun (Shorea aeuminata), Meranti Kepong (Shorea ovalis), Meranti Nemesu (Shorea paueiflora), Meranti Melantai (Shorea maeroptera), Meranti Pa'ang (Shorea braeteolata), Meranti Pipit (Shorea assamieaf globifera). From this study, it was found UiTMJFR is suitable for plantation of Meranti Species because UiTMJFR is type of Lowland Dipterocarp Forest. We can see that 89% is category on Red Meranti, for the percentage of White Meranti is 11%. From this result we can say that UiTMJFR is suitable for Red Meranti plantations in the future.